In-situ crosslinking of Aspergillus flavus lipase: improvement of activity, stability and properties - Long, Kamariah; Mohd Ghazali, Hasanah; Ariff, Arbakariya; Ampon, Kamaruzaman; Bucke, Christopher (Kluwer Academic Publishers, 1996)
The mycelium-bound lipase of Aspergillus flavus was stabilised by cross-linkage using glutaraldehyde or methylglyoxal. Lipase activity was enhanced by up to 48% by treatment with methylglyoxal but not by glutaraldehyde. Cross-linking with methylglyoxal increased the thermal stability of the lipase by 58% at 50°C.